A Randomised Controlled Trial of an Sms-Based Mobile Epilepsy Education System. (January 2013) - Lua, Pei Lin; Neni, Widiasmoro Selamat
We evaluated an epilepsy education programme based on text messaging (SMS). Epilepsy outpatients from three hospitals in Malaysia were randomised into two groups: intervention and control. Patients in the control group were supplied with printed epilepsy educational material while those in the intervention group also received text messages from the Mobile Epilepsy Educational System (MEES). A total of 136 patients completed the study (mean age 31 years; 91% Malay; 51% with an illness duration of more than 5 years). A between-group analysis showed that the awareness, knowledge and attitudes (AKA) about epilepsy did not significantly differ between the groups at baseline ( P > 0.05). The intervention patients reported better AKA levels during follow-up compared to the control patients ( P < 0.05). A within-group analysis showed that in intervention patients, there were significant improvements in all AKA domains with larger effect sizes ( P < 0.01) while control patients also exhibited significant improvement in most domains except for Awareness but with smaller effect sizes. After controlling for possible confounding variables (age, gender, educational qualification, monthly income and baseline mean for each domain), the intervention group still reported significantly higher AKA than the control group particularly in Awareness ( P < 0.001) and Total AKA ( P = 0.003). There was also significantly better medication adherence and clinic attendance in the intervention group ( P < 0.05). The results suggest that the addition of the MEES to conventional epilepsy education is effective in improving AKA.